The Study of Success in Driving the Philosophy of Sufficiency Economy A Case Study o - Kenamang, Yuwadee; Wongwatthanaphong, Kampanart (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
The objectives of this research were 1) to study the level of success driving the sufficiency economy philosophy, 2) to compare the differences of personal factors with the success of driving the sufficiency economy philosophy, and 3) to study the proposals for the success of the sufficiency economy. Driving the Philosophy of Sufficiency Economy: A Case Study of the Sufficiency Economy Learning Center and Drive the Philosophy of Baan Srinakorn, Srinakorn Sub-district, Srinakorn District, Sukhothai Province. For the quantitative data, a sample sample was used to represent the population, namely 135 committee members and members of the Srinagar Sufficiency Economy Learning and Driving Center, calculated using Taro Yamane’s formula at 95% confidence level and qualitative data. use The main contributors were the committee and members of the Sufficiency Economy Learning Center and the Philosophy of Baan Srinakorn and Community Development Officers in Srinakorn Sub-District, totaling 5 persons. The researcher chose to use statistics for data analysis as follows: Descriptive statistics. The data were analyzed by frequency, percentage, mean, standard deviation, t-test and One-Way ANOVA. The results of the study were as follows: 1) the degree of success in driving the philosophy of the sufficiency economy Overall, the average was at a high level. 2) Personal factors. Status within the center Different Affect the success in driving the philosophy of the sufficiency economy. Case Study of Sufficiency Economy Learning Center and Driving Center at Baan Srinakorn, Srinakorn Sub-district, Srinakorn District, Sukhothai Province The method for increasing the success in driving the sufficiency economy philosophy of Baan Srinakorn, Srinakorn Sub-district, Srinakorn District, Sukhothai Province is the role of the Sufficiency Economy Learning Center in strengthening the community. It helps to foster the development and change the vision of the people in the community as well. Learning activities result in self-reliance. Self management and can actually strengthen the household and community.